Proceedings of the 8th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2016
DOI: 10.1145/3003715.3005417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Haptic Patterns on a Steering Wheel

Abstract: Infotainment Systems can increase mental workload and divert visual attention away from looking ahead on the roads. When these systems give information to the driver, provide it through the tactile channel on the steering, it wheel might improve driving behaviour and safety. This paper describes an investigation into the perceivability of haptic feedback patterns using an actuated surface on a steering wheel. Six solenoids were embedded along the rim of the steering wheel creating three bumps under each palm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Most of the current information is presented audio-visually [1] on the center stack or instrument cluster. This means that the driver needs to shift their attention from the primary driving task to interact with input elements for common tasks (e.g., turning on the windscreen wipers in a Tesla Model 3/Y) which can be dangerous [7,8]. Although efforts have been made to include physical buttons and switches (i.e., on steering wheels) for specific tasks, dedicated buttons are limited in design by their functionality and often require some visual attention from the central stack.…”
Section: Steering Wheel Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current information is presented audio-visually [1] on the center stack or instrument cluster. This means that the driver needs to shift their attention from the primary driving task to interact with input elements for common tasks (e.g., turning on the windscreen wipers in a Tesla Model 3/Y) which can be dangerous [7,8]. Although efforts have been made to include physical buttons and switches (i.e., on steering wheels) for specific tasks, dedicated buttons are limited in design by their functionality and often require some visual attention from the central stack.…”
Section: Steering Wheel Interactionmentioning
confidence: 99%
“…Ideally, dynamic touch surfaces [9] on the steering wheel that can be used as both haptic input and output can complement visual and auditory information provided from the onboard displays / HUDs within the vehicle. However, providing reliable tactile output, without signal attenuation and integration on the steering wheel in a moving vehicle has been quite challenging [10][11][12]30] due to 1) limitation in actuation components, 2) mediation of signals to the point of contact, and 3) mitigating environmental noise. In the present work the focus is on solving these challenges by using 3Dprinted Embedded Haptic Waveguides (EHWs) [13][14][15] within the steering wheel to mediate the tactile feedback from the actuator to the point of contact.…”
Section: Steering Wheel Interactionmentioning
confidence: 99%
“…In further studies, they showed that the thenar region, the base of the thumb, was preferred by most participants and caused a lower error rate. Engaging one pin showed 92.2% accuracy [9]. We adapted this feedback type for our second study and used it for navigation for the first time and compared its performance to that of thermal feedback.…”
Section: Haptic Feedback In the Carmentioning
confidence: 99%
“…It would be good to focus some work on individual private spaces" (Frangakis et al 2014). There are also issues regarding how interaction should be supported in transit (Ng and Brewster 2016;Shakeri et al 2016), whilst, most fundamentally of all, there is the "elephant in the room" of motion sickness which, particularly with road-based transit, has the potential to significantly impede passenger adoption and usage of technology (McGill et al 2017). Looking out of windows is a common, necessary and often enjoyable way to minimize motion sickness-albeit at the expense of disrupting any non-travelrelated activities.…”
Section: Introductionmentioning
confidence: 99%